2004
DOI: 10.1111/j.1365-2672.2004.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

The ability of two different Vibrio spp. bacteriophages to infect Vibrio harveyi, Vibrio cholerae and Vibrio mimicus

Abstract: Aims: To determine the host range of the Vibrio harveyi myovirus-like bacteriophage (VHML) and the cholera toxin conversion bacteriophage (CTX U) within a range of Vibrio cholerae and V. mimicus and V. harveyi, V. cholerae and V. mimicus isolates respectively. Methods and Results: Three V. harveyi, eight V. cholerae and five V. mimicus isolates were incubated with VHML and CTX U. Polymerase chain reaction (PCR) was used to determine the presence of VHML and CTX U in infected isolates. We demonstrated that it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The determination of the complete DNA sequence of the prototype phage VP58.5 revealed very strong similarity to phage VHML. Besides V. harveyi strains, VHML has been reported to lyse the strains Vibrio alginolyticus ACMM102 and Vibrio cholerae ATCC 14035, but there are no published data on the infectiousness for V. parahaemolyticus (33). On the other hand, we could not find a V. harveyi strain susceptible to VP58.5.…”
Section: Discussioncontrasting
confidence: 49%
“…The determination of the complete DNA sequence of the prototype phage VP58.5 revealed very strong similarity to phage VHML. Besides V. harveyi strains, VHML has been reported to lyse the strains Vibrio alginolyticus ACMM102 and Vibrio cholerae ATCC 14035, but there are no published data on the infectiousness for V. parahaemolyticus (33). On the other hand, we could not find a V. harveyi strain susceptible to VP58.5.…”
Section: Discussioncontrasting
confidence: 49%
“…Oakey and Owens found that VHML has a narrow range and only infected four of the 36 strains tested. However, some other species of Vibrio, notably V. cholerae (ACM #2773/ATCC #14035) outside the Harveyi clade [19] and V. alginolyticus [16] could be infected by VHML. Of note was that the strains of the Harveyi clade successfully infected were mostly different between the two bacteriophages.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, V. harveyi myovirus like (VHML) particles are reported to be associated with virulence in V. harveyi (Munro et al, 2003). Nine (5 isolates recovered from infected larvae and 4 from water samples) of V. harveyi isolates obtained during the LB disease outbreak in the present study were screened for VHML by polymerase chain reaction (PCR) (Payne et al, 2004) (data not given) and none of these isolates produced the 900 bp product specific for tail sheeth encoding gene of VHML (instead, a 350 bp fragment could be amplified). Occurrence of luminous vibriosis in larval shrimp by LB isolates that lack VHML suggests possibilities of involvement of other bacteriophages similar to VHML in the virulence of V. harveyi.…”
Section: Discussionmentioning
confidence: 99%